Menganalisis Karateristik Kreativitas dalam Pembelajaran Kreatif dan Inovatif di SD N 064966 - Talenta Siahaan; Suyit Ratno; Keysha Nadadap; Ira Sihotang; Sara Manurung; Salman Laia; Johan Lase (Universitas Maritim AMNI Semarang, 2024)
Research aims to analyze the characteristics of students' creativity in creative learning of SDN 064966 innovation. Through participant observation and in-depth interviews with students and teachers, it was found that the dominant characteristics of creativity include fluency, flexibility, originality, and idea creativity. Explain Apart from that, another benefit of research is to classify the factors inhibiting and supporting the development of student creativity in the school learning environment. It is hoped that the results of this research can contribute to the development of learning models that are more effective in fostering student creativity.